Impact of Microfinance on Women’s Entrepreneurship - Bosu, Champa (Archives of Business Research, 2023)
Microfinance (MF) and its institution’s contribution to poverty reduction, alleviation, and eradication through entrepreneurship has been a debatable issue until now. Especially some controversial roles of the traditional microfinance institutions in different ‘global south’ countries made the situation even more complicated and problematic. Some recent scientific studies and global media reports against the role of microfinance in reducing poverty have given us some space for thoughts on the role of traditional microfinance institutions in entrepreneurship development among rural women. However, many scientific studies and media reports have claimed that microfinance contributes to a reduction in poverty through entrepreneurship by traditional microfinance institutions or commercial banks. However, it is unclear if MF is the most efficient way to reduce poverty without the help of other additional procedures among the poverty-stricken people or areas such as education, politics, health, infrastructure, etc. In the current paper, a critical observation has been made on the roles of microfinance in entrepreneurship development among poor, marginalized women. A literature survey has been made using different sources, such as academic databases, media reports, I/NGO reports, etc. It was found that some of the women who have received loans through microcredit or microfinance institutions used the money for consumption; however, most of the women recipients used the loan for their entrepreneurial activities or businesses to change their financial condition and have successfully brought financial sustainability.